Typological Differentiation of Workers of the Rolling Stock Repair Plant in Poznań in the Light of Wanke’s Typology - Bednarska, Halina; Drozdowski, Zbigniew; Ziółkowska, Ewa (Anthropological Review, 1987)
In a team of 164 workers working hard in the repair plant of the rolling-stock anthropometric studies were carried out aiming at typological determination in the light of A. Wanke’s system. It was found that in the investigated group the A element was the prevailing one (30.14%),next came the I element (28.78%), immediately afer followed the V element (24.34%), while the H element was the least numerous one (16.74%). Since the studied group consisted mainly of people originating from the country it seems that a different migrational dynamism of the particular somatic types is possible.